Novel mutations in TGM1 and ABCA12 cause autosomal recessive congenital ichthyosis in five Saudi families. (7th April 2016) - Wakil, Salma M.; Binamer, Yousef; Al‐Dossari, Haya; Al‐Humaidy, Rawan; Thuraya, Rula Al; Khalifa, Ola; Finsterer, Josef; Meyer, Brian F.; Al Owain, Mohammed
Abstract: Background: Autosomal recessive congenital ichthyosis (ARCI) is a rare disorder of keratinization. Infants (10–15%) born with this condition are encapsulated in hyperkeratotic membrane covering the entire body and are called "collodion babies." So far, mutations in nine different genes have been identified as causative and implicated in the pathogenesis of the clinically and genetically heterogeneous group of ARCI disorders. Among these, TGM1 is the gene most commonly mutated in ARCI. Methods: We identified 11 patients from five consanguineous but unrelated families affected by ARCI. These patients manifested thick adherent polygonal large scales all over the body. All six patients with TGM1 mutations were born with collodion membrane and had ectropion and eclabium, while none of the patients with ABCA12 mutations had these features. Molecular investigations were performed using the combined approach of homozygosity mapping and Sanger sequencing. Results: Here we report two novel mutations c.397_398insAGTATGAGTA (p.Tyr136Ter) ; c.977‐978delCT (p.Ser326Cysfs*8) in TGM1 in three different, unrelated Saudi families and one novel mutation c.6900C>A (p.Phe2300Leu) and one reported mutation c.3470C>T (p.Ser1157Leu) in the ABCA12 gene in two unrelated Saudi families with ARCI. Conclusions: The identification of these homozygous variants using combined approaches of homozygosity mapping with direct sequencing are the disease causing mutations in these families. Furthermore, these findings are essential for the genetic diagnostic and prognostic workup with ARCI in Saudi patients.